2016
DOI: 10.1097/bot.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Early Weightbearing and Range of Motion Versus Non-Weightbearing and Immobilization After Open Reduction and Internal Fixation of Unstable Ankle Fractures: A Randomized Controlled Trial

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(196 citation statements)
references
References 17 publications
4
189
1
2
Order By: Relevance
“…The participants in the study had stable, anatomically adequate fixation of the distal fibula and/or medial malleolus prior to being included in the trials. Recent studies on early weight-bearing of surgically treated fractures of the ankle joint showed good outcome and even a lower rate of plate removal (31,32). In one radiostereometric study with fractures of the tibial plateau, the mean cranio-caudal migration of the fracture fragments at 1 year after the start of early weight-bearing was insignificant -0.34 mm (-1.64 to 1.51) (33).…”
Section: Resultsmentioning
confidence: 99%
“…The participants in the study had stable, anatomically adequate fixation of the distal fibula and/or medial malleolus prior to being included in the trials. Recent studies on early weight-bearing of surgically treated fractures of the ankle joint showed good outcome and even a lower rate of plate removal (31,32). In one radiostereometric study with fractures of the tibial plateau, the mean cranio-caudal migration of the fracture fragments at 1 year after the start of early weight-bearing was insignificant -0.34 mm (-1.64 to 1.51) (33).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, other advantages (i.e., prevention of muscle wasting and osteoporosis) are expected. However, these effects have not been investigated thus far [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…For ankle fracture, early weight bearing after ORIF is feasible biomechanically without loss of reduction or fixation failure [28]. Dehghan et al [16] designed a multicenter RCT, 110 patients with an unstable ankle fracture underwent ORIF, they were randomly divided into two groups, in the early weightbearing group, patients started full weightbearing at 2…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively reviewed patients who were diagnosed as SER IV ankle fractures (AO/OTA classification 44-B3.1), they underwent surgical treatment between January 2012 and December 2015. The inclusion criteria were as follows: patients underwent ORIF with TEF or ORIF with DLR, pre-and postoperative X-rays evaluation, a preoperative magnetic resonance imaging (MRI) and three-dimensional computed tomography (CT), patients greater than 16 A total of 745 ankle fractures treated operatively were identified initially. 584 were excluded because of multiple and open fractures, 23 old fractures were also excluded, 78 were excluded because of no MRI examination, 17 were excluded because of loss of follow-up.…”
Section: Methodsmentioning
confidence: 99%